PORTAL VEIN THROMBOSIS AND CAVERNOUS TRANSFORMATION IN TWO PATIENTS WITH PEPTIC ULCER - Gonca TATAR,; Esin ÖZYILKAN,; Ferhun BALKANCI,; Burhan KAYHAN,; Hasan TELATAR, (Turkish Journal of Gastroenterology, 2020)
-